ANALYSIS OF FINANCIAL AT THE PERFOMANCE SAKO JATI SUB-DISTRICT PANGEAN DISTRICTS KUANTAN SINGINGI - Jerni Laila; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the financial performance of the Soko Jat Plantation Cooperative in the Pangean District of Kuantan Singingi Regency in the 2014-2018 period in terms of the analysis of Liquidity Ratios, Solvency, Profitability, and Activity methods used are descriptive quantitative methods. Research data and information were obtained from the Sako Jati Plantation Cooperative in the district of Kuantan Singingi, located in Soko Village, Pangean District, Kuantan Singingi Regency.From the data analysis using liquidity ratio analysis it can be concluded that for Liquidity Ratios with the Current Ratio indicator are in poor criteria with an average of 790.4% and Cas Ratio are in poor criteria with an average of 96.956%. Solvency Ratio with Debt to Asset Ratio indicator is in bad criteria with an average of 90,694% and Debt to Equity Ratio is in bad criteria with an average of 931,55%. The Profitability Ratio with the Retrun On Asset indicator is in good enough criteria with an average of 4.456% and the Retrun On Equity is in a very good criterion with an average of 38.034%. And the Activity Ratio using the Total Asset Trunover indicator is in poor criteria with an average of 0.084%. Keywords: Analysis, Liquidity, Solvency, Profitability, Activi